Konsep Jual Beli Dalam Perspektif Al-Quran Dan Al-Sunnah (Urgensitas Penerapan Prinsip Halalan Thayyiban sebagai indikator dalam Mengukur Hukum Keabsahan terhadap Praktik Jual Beli) - Acep Faizal Ramdan; Neli Purnamasari (Mutawasith: Jurnal Hukum Islam, 2020)
This research is based on the fact that the majority of Indonesian Muslims do not yet understand the concept of good buying and selling perspective of the Quran and Al-Sunnah. The concept of buying and selling that they understand is only for the fulfillment of the buyer's needs, and to pursue the seller's profit, without considering the maslahat and its mafsadat. The purpose of this research is to describe the urgency of the principle of halalan thayyiban in the concept of buying and selling according to the Quran and Al-Sunnah. The method used is descriptive, by presenting the concept of buying and selling according to the perspective of the Quran and Al-Sunnah, while the data collection technique is a study of libraries from journals and books related. The results showed that the sale of halalan tayyiban was a necessity because it was part of the terms of the trade. The trade transaction is not halal and good then the sale becomes bathi. The basis of the law of buying and selling with halalan thayyiban is Q.S. al-Baqarah: 172-173 and hadeeth by Bukhari Muslim in the book of Bulughul Maram hadeeth to 801, on the prohibition of buying and selling.